Uso de micorrizas en el cultivo de sandía Citrullus lanatus L - Moscoso Aldaz, Jefferson Marlon (2022)
Mycorrhizae are soil microorganisms, which represent the association between some fungi and the roots of plants that act as fertilizers, improving agricultural production. The term mycorrhizae was used in the 19th century to refer to a group of fungi. They are involved in symbiosis with the roots of higher plants and it is estimated that mycorrhizae have performed their function with plants for 370 million years. Today there are many different types of mycorrhizal fungi, and most of them can be found on the roots of different plants; the function of mycorrhizae in plants, similar to nitrogen-fixing rhizobia in legumes, is more effective in plants with thicker roots than those with thinner roots. What was collected allowed to identify that the use of mycorrhizae contributes to improve the agronomic characteristics of the plant, as well as its nutritional level, reflected in the increase in yields; abscular mycorrhizae can protect plants from pests and diseases, against the attack of various pathogens found in the soil; the phenomenon of mycorrhizal symbiosis helps to increase the absorption of nutrients and water in plants, promoting greater growth and development of watermelon plants and mycorrhizal inoculation in the watermelon crop at the time of sowing, transplanting and 15 days after transplanting , significantly increases the length of the main guide, the fresh weight of the plant and the length and weight of the roots of the watermelon plants.